Kohesi Gramatikal pada Tajuk Rencana Surat Kabar Haluan Riau - Pertiwi, Devi; Hermaliza, Hermaliza (UIR PRESS, 2023)
Newspaper is one of the print media that is used to obtain various kinds of information. Information that can be conveyed must use the Indonesian language which is easy to understand and in accordance with the rules of the Indonesian language properly and correctly. This study aims to collect data and information about the grammatical cohesion of pronouns in the editor of the bow riau newspaper. The collected data and information will be described, analyzed, and researched in detail and systematically so that the actual situation regarding grammatical cohesion in the editorial section of the Riau newspaper can be identified. The data of this study are words or phrases that have grammatical cohesion in Riau's bow newspapers. To find data in newspapers, you need to be careful and every problem in newspapers only gets. Based on the analysis of the data presented, it can be concluded that grammatical cohesion in the editorials of the Haluan Riau newspaper, namely, grammatical cohesion in the editorials of the Riau Haluan newspaper in the December 2020 and January 2021 editions uses many pronouns which include personal pronouns, demonstrative pronouns , possessive pronouns, questioning pronouns, connecting pronouns, and indefinite pronouns.